Preparation and optical properties of CaYAl3O7:Eu2+, Dy3+ phosphors with blue long afterglow luminescence. (15th September 2022) - Sun, Dongwei; Zeng, Qingling; Zhou, Yongyan; Tang, Nian; Du, Hongli; Zhang, Manjun; Guo, Dongcai
Abstract: In this paper, a new blue long afterglow luminescent material CaYAl3 O7 :Eu 2+, Dy 3+ was prepared by high-temperature solid-phase method. The physical phase analysis was carried out by X-ray diffraction; the elemental valence analysis was conducted by X-ray photoelectron spectroscopy; the luminescence properties of the samples were characterized by fluorescence spectrometer and UV absorption spectrometer; and the afterglow properties were measured by afterglow spectrometer. The results show that the doping of Eu 2+ and Dy 3+ did not change the physical phase of the crystals. In this long afterglow material, the introduction of Dy 3+ as a trap center did not change the shape of the excitation and emission spectra of the samples, but the afterglow brightness can be significantly enhanced. The best afterglow performance was achieved when the doping concentration of Dy 3+ was 1%, with an afterglow time of 109 min for a brightness greater than 3.2 mcd/m 2 discernible to the naked eye. Highlights: A new blue long afterglow luminescent material CaYAl3 O7 :Eu 2+, Dy 3+ was prepared by high-temperature solid-phase method. The XRD, XPS, UV-VIS, PL, PLE, afterglow and luminescence mechanism of the synthesized samples were specifically analyzed. The afterglow performance of CaYAl3 O7 :Eu 2+ was significantly improved by co-doping Dy 3+ as a trap center.